Penetapan kadar vitamin C dalam sirup buah naga merah (hylocereus polhyrizus) dengan variasi waktu penyimpanan - Laili, Miftachul; Alimuddin, Alimuddin; Erwin, Erwin (Jurusan Kimia FMIPA UNMUL, 2017)
A research on the determination of a level of vitamin C in Red Dragon fruit syrup by conducting storage time variety have been done in normal condition so that it can be consumed. Analysis process has been conducted by Iodimetry titration method through the step of dragon fruit syrup made by the variety of storage time 0 until 20 days. The result showed that high level of vitamin C was 0.03136 % on the beginning day, and the low level was 0.00141 % on the 20th, therefore can be summaries that vitamin C on dragon fruit syrup product can last while 20 days only in the normal condition. Furthermore, for an organoleptic test of the dragon fruit syrup product can last on the beginning day until the day of 15th and on the day of 16th or more that respondents declare of dragon fruit syrup, product was not feasible to consumed.